An Unusual Case of Primary Gastric Balloon Cell Melanoma. Issue 2 (9th February 2023) - Chaudhry, Hunza; Green, Victoria; Lin, Joanne; Lewis, Justin; Wong, Helen
ABSTRACT: Most cases of melanoma found in the gastrointestinal tract are the result of metastasis. Although uncommon and only described in isolated case reports, primary gastric melanoma should be considered when patients present with vague gastrointestinal symptoms and a mass is identified on esophagogastroduodenoscopy or imaging. We describe a case of primary gastric balloon cell melanoma in a 73-year-old man who presented with melena. Given the high morbidity and mortality of gastric mucosal melanoma, early diagnosis and initiation of treatment can lead to improved outcomes and survival.